Pengaruh Spaylater dalam Online Shop terhadap Perilaku Konsumtif Pada Mahasiswa Muslim di FEBI UINSU - Muhammad Satrya Mutthaqin; Patma Wati; Chuzaimah Batubara (Universitas Muhammadiyah Surabaya, 2023)
AbstractPaylater is increasingly popular among millennials along with the development of technology. These technological advances have had a very significant impact on the survival of society, especially the millennial generation, who will become more consumptive through the arrival of electronic or non-cash payment instruments, without cash, this will form impulsive shopping behavior where a person buys products without planning. This research was conducted to see the effect of SPaylater on consumptive behavior of students at the Faculty of Islamic Economics and Business, State University of North Sumatra. This study used a quantitative method with data collection techniques using a questionnaire. The results showed that the use of SPaylater on FEBI UINSU students influenced consumptive behavior.Â Keywords: SPaylater, Consumptive Behavior